Peran Devidend Policy Pada Solvensi dan Kinerja Keungan Terhadap Nilai Perusahaan - Marista Oktaviani; Tyasha Ayu Melynda Sari; Adhar Putra Setiawan (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2023)
This research is a descriptive research with a quantitative approach. The sample is a consumer goods industrial company. The data collection method used purposive sampling. The data analysis technique used is SEM model analysis with SmartPls analysis tool. The results showed that the current ratio had a significant positive effect on firm value and earnings per share had no effect on firm value. Dividend policy in this study is used as a moderating variable. The results of the dividend policy moderate the relationship between the current ratio and earnings per share on firm value.